Civic practice: A new professional paradigm for social work. (March 2014) - Harington, Philip RJ; Beddoe, Liz
Summary: Economic rationalism has had an impact upon the position of many professions in Western society. Drawing on New Zealand material this article argues that neoliberal targeting of professions' capacity to capture domains of service and their funding has fuelled deprofessionalization, but also created space for alternative domains of practice. A case for a civic model of social work practice is argued.  Findings: Debates about the nature of professions flourish in current literature. An exploration of the features of the social work profession suggests three types: heroic, altruistic and civic. The development of civic practice in social work is suggested, presupposing a reframing of the role and focus of the profession toward social inquiry applied to the rights and needs of citizens.  Application: The contribution of this article is to explore a move forward in the de-professionalization debates and to propose a civic social work grounded in advocacy and critical social inquiry.